KOMUNIKASI PEMERINTAHAN DESA DALAM UPAYA PENANGANAN COVID 19 DI DESA PERHENTIAN LUASKECAMATAN LOGAS TANAH DARAT KABUPATEN KUANTAN SINGING TAHUN 2020-2021 - Ibnu Sectio Riveldi; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
In accordance with the Decree of the Regent of Kuantan Singingi Number: KPTS. /I/2021 regarding the Formation of a Preparatory Team for Corona Virus Disease 2019 Vaccination in Kuantan Singingi Regency and the Instruction of the Kuantan Singingi Regent Number: 480/INS/2021/635 concerning Implementation of Activities for Countermeasures and Management of Corona Virus Disease 2019 (Covid 19). If the vaccine is evenly distributed, it will be a little easier to eliminate Covid 19 if all parties involved want to work together and communicate well. The purpose of this study is to describe the communication carried out by the Village Government in an effort to deal with Covid 19 and describe the inhibiting factors in Village Government communication for handling Covid 19 in Perhentian Vast Village, Logas Tanah Darat District, Kuantan Singingi Regency. The results and discussion of this study show that the communication carried out by the Village Administration in an effort to handle Covid 19 in Perhentian Luas Village, Logas Tanah Darat District, Kuantan Singingi Regency is still minimal and has not gone well where the Covid Volunteer team or the Covid Care Task Force formed by The Village Head is still lacking in providing guidance and counseling to the community for handling Covid 19 and this is compounded by the lack of awareness and understanding of the Village community about how to handle Covid 19 which has been made by the Village Government. Perhentian Broad Village Government should be able to prevent Covid 19 by good communication with the community. There are several factors inhibiting communication carried out by the Village Government for handling Covid 19 in Perhentian Luas Village, namely: Facility and Infrastructure Factors, Personal Barriers, Barriers to rules and sanctions, and Economic Barriers. Keywords: Village government communication, Handling Covid 19